Analysis of early surgical indications and related factors in neonatal necrotizing enterocolitis - Shang, Xianhui; Wang, Huinan; Liu, Yuanmei; Yang, Xuefeng; Huang, Lu; Fu, Hao; Xiang, Luping; Xu, Shiyu (Frontiers in Pediatrics, 2025)
ObjectiveTo explore early surgical indications and clinical predictive factors for neonatal necrotizing enterocolitis (NEC) to improve the prognosis of affected infants.MethodsA retrospective analysis was conducted on the clinical data of 146 infants diagnosed with NEC at the Affiliated Hospital of Zunyi Medical University from January 2015 to December 2020. The infants were divided into two groups: the surgical treatment group (56 cases) and the non-surgical treatment group (90 cases). Maternal perinatal conditions, general infant characteristics, clinical manifestations, comorbidities, laboratory tests, and imaging findings were statistically analyzed. Significant factors were further analyzed using multivariate logistic regression, and predictive indicators were assessed by the receiver operating characteristic (ROC) curve and Youden's index.ResultsStatistically significant differences were observed between the two groups in birth weight, gestational age, abdominal wall erythema, absent bowel sounds, lethargy, fever, peritonitis, septic shock, metabolic acidosis, neonatal acute respiratory distress syndrome, and asphyxia (P < 0.05). No significant differences were found in maternal perinatal conditions, sex, feeding method, age at onset, abdominal distention, bloody stool, vomiting, gastric retention, apnea, neonatal pneumonia, neonatal hyperbilirubinemia, sepsis, electrolyte disturbances, or respiratory failure (P > 0.05). Laboratory and imaging markers such as prealbumin, IL-6, PCT, CRP, WBC, pneumoperitoneum, bowel wall gas, and portal venous gas showed statistically significant differences (P < 0.05). Multivariate logistic regression identified peritonitis (OR = 95.635), IL-6 (OR = 1.001), and portal venous gas (OR = 22.551) as independent risk factors for early surgery in NEC (P < 0.05). ROC curve analysis revealed that IL-6 (AUC = 0.875) and PCT (AUC = 0.798) demonstrated good predictive performance for early surgical intervention. The optimal cutoff values were 476 pg/ml for IL-6 (sensitivity 80.4%, specificity 85.6%) and 1.53 ng/ml for PCT (sensitivity 83.9%, specificity 70%).ConclusionPeritonitis and portal venous gas are independent risk factors for early surgery in NEC. IL-6 and PCT are reliable predictive markers for determining the need for early surgical intervention in NEC.